The Rock and Boulder Gardens: a Rock Labyrinth in the Rocky Mountains - Hincks, Karen; Cruden, David (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 2004)
AbstractA rock labyrinth in the Devonian Palliser Formation, which dips at 24° in the direction 224°, occurs in the Front Ranges of the Rocky Mountains, 5 km northeast of the town of Jasper, Alberta. The area that composes the Rock and Boulder Gardens, 200 m by 500 m in size, is visible on aerial photographs of the Maligne Valley. The labyrinth is distinguished by the regular arrangement of large blocks of carbonates that are separated by widely-gaping joint planes. Kinematic freedom for the translation of these blocks was created when erosion of the south slope allowed blocks to slide out of the hanging Maligne Valley into the Athabasca Valley. The rock labyrinth is believed to have formed under periglacial conditions, driven by the build up of snow in open joints exerting a downslope force on blocks.